2013
DOI: 10.1017/s146342361300025x
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss surgery for non-morbidly obese populations with type 2 diabetes: is this an acceptable option for patients?

Abstract: AimTo explore the views of non-morbidly obese people (BMI 30–40 kg/m2) with type 2 diabetes regarding: (a) the acceptability of bariatric surgery (BS) as a treatment for type 2 diabetes, and (b) willingness to participate in randomised controlled trials comparing BS versus non-surgical intervention.BackgroundDespite weight management being a key therapeutic goal in type 2 diabetes, achieving and sustaining weight loss is problematic. BS is an effective treatment for people with morbid obesity and type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Almost half of the patients were "neutral" or had "no opinion" about how well BS would improve TDM2, and only a minority of patients believed that BS was a safe treatment for T2DM and <20% of respondents indicated willingness to participate in a randomized research study of BS. Semistructured interviews performed by Summers et al on a similar cohort found that most subjects would consider to take part in such studies only if they were assigned to the medical treatment arm [47]. The most influential themes to determine the individual's stance on the appropriateness of BS were 'condition-related life impact' (perceived threat of metabolic syndrome to their own health and well-being) and 'perceived control' (feeling incapable to exert weight loss or control comorbidities).…”
Section: Implementation Of Bariatric Surgery Into the Health-care Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost half of the patients were "neutral" or had "no opinion" about how well BS would improve TDM2, and only a minority of patients believed that BS was a safe treatment for T2DM and <20% of respondents indicated willingness to participate in a randomized research study of BS. Semistructured interviews performed by Summers et al on a similar cohort found that most subjects would consider to take part in such studies only if they were assigned to the medical treatment arm [47]. The most influential themes to determine the individual's stance on the appropriateness of BS were 'condition-related life impact' (perceived threat of metabolic syndrome to their own health and well-being) and 'perceived control' (feeling incapable to exert weight loss or control comorbidities).…”
Section: Implementation Of Bariatric Surgery Into the Health-care Systemmentioning
confidence: 99%
“…Based on the current literature review, mindset barriers of BS seem to be mainly related to the lack of information, to incorrect information and to weight bias (Table 2) Table 1. Patient-related mindset factors in favor and against seeking bariatric surgery Facilitator for seeking BS Barriers for seeking BS "surgery-for-health" concept [39] "surgery-for-weight-loss" concept [39] e-information provided by public hospitals or other patients [31] never heard of bariatric surgery [20] educational seminar in bariatric centers [35] failure to recognize themselves as morbidly obese [20] higher confidence in decision making [37] primary care physicians did not recommend BS [20] bariatric insurance «rider» [37] [34] believes BS to be a cosmetic procedure [29] poorer obesity-related quality of life [37] worries about the risks [37] metabolically more compromised state [36], [34], [38], [47] Table 2. Knowledge and mindset barriers in the diffusion of bariatric surgery (BS) in the general population, among potential candidates and among primary care physicians (PCP).…”
Section: Future Outlook and Potential Strategies To Address Mindset Bmentioning
confidence: 99%
“…Evidence on acceptability and willingness to participate in UK bariatric surgery trials in this group is needed to indicate feasibility and support decision making amongst researchers and funders. Our qualitative study of patient perceptions in a United Kingdom (UK) sample, suggested that there was interest in bariatric surgery amongst this group and that certain perceptions might influence willingness to participate; specifically, the impact of their weight on life, impact of diabetes on life, ability to control their weight, ability to control their diabetes and satisfaction with their ability to lose weight, [18]; however, willingness amongst this group on a representative level is unknown. This study aimed to quantify the perceptions of patients with a BMI 30-39.9kg/m 2 and T2DM in England, on their weight, diabetes, and their willingness to participate in bariatric surgery RCTs.…”
Section: Introduction/purposementioning
confidence: 97%
“…This study aimed to quantify the perceptions of patients with a BMI 30-39.9kg/m 2 and T2DM in England, on their weight, diabetes, and their willingness to participate in bariatric surgery RCTs. A self-completion questionnaire was developed based on data collected from a previous qualitative study [18]. and 25% of eligible patients being selected randomly using computer generated numbers in practices identifying 50-149, or 150 or more patients, respectively.…”
Section: Introduction/purposementioning
confidence: 99%
“…Patients who had experienced adverse effects of T2D or overweight were more likely to consider weight loss surgery. 7 Another cross-sectional study among T2D patients with BMI 30-40kg/m 2 in the USA, around one-third perceived bariatric surgery to be very effective for obesity treatment and 28.5% T2D patients thought that bariatric surgery was effective in T2D treatment. Around 8% said its ineffective T2D management.…”
Section: Introductionmentioning
confidence: 99%